Modern Diagnosis and Treatment of Myocardial Infarction - N. Sh., Toshnazarova; Shahrizoda Khasan Qizi, Sayfiyeva (Journal of Science in Medicine and Life, 2026)
Myocardial infarction is a critical clinical form of ischemic heart disease that occurs due to the complete or partial occlusion of a coronary artery, leading to the irreversible necrosis of heart muscle tissue. It remains a leading cause of global mortality, with particularly high death rates recorded in Russia, Ukraine, and the USA. Despite its prevalence, a significant challenge exists in diagnosing "silent" or painless infarctions, which occur in 9% to 50% of cases, primarily among elderly patients and those with diabetes. Furthermore, gender-based diagnostic disparities are evident as women frequently present with atypical symptoms such as back pain, dizziness, or unusual fatigue, often leading to dangerous delays in seeking emergency medical attention. This study evaluates diagnostic and therapeutic efficacy using a combination of clinical symptomatology, electrocardiography ECG to distinguish between ST-elevation and non-ST-elevation NSTEMI events, laboratory markers such as high-sensitivity cardiac troponin, and instrumental interventions including angioplasty and stenting. The research indicates that while typical retrosternal pain remains the primary hallmark, successful management relies heavily on the "Golden Hour" principle. Immediate reperfusion therapy—ideally through Percutaneous Coronary Intervention within 120 minutes—is critical for saving the myocardium and preventing heart failure. Rapid intervention significantly determines survival; patients receiving early reperfusion show markedly better outcomes and lower mortality compared to those with delayed treatment. Conversely, factors like advanced age, diabetes, and delayed reperfusion severely worsen the long-term prognosis. To reduce the 30% mortality rate associated with acute MI, public health strategies must focus on a dual approach: advancing high-tech surgical interventions like stent placement and coronary artery bypass grafting, while simultaneously improving public awareness regarding atypical symptoms and the importance of both primary and secondary prevention through lifestyle modification and long-term pharmacotherapy.